Modelo para implementar la Norma Técnica de Gestión NTC 6001, Empresas Mypes (2016)
The model facilitates the implementation and certification management system NTC 6001 micro and small enterprises (MSEs), equivalent to the NTC ISO 9001, designed for all sizes of company; MSEs unable to demonstrate that implementation has been affecting them when in the selection process require suppliers to be certified, MSEs have shortages in resources for the process to implement and achieve certification; ICONTEC, designed the NTC management standard 6001 for MSEs, with which achieved business formality, legal regulations, improving administrative, operational and support processes; its implementation is achievable, contributes to the quality, safety, satisfaction, low uncertainty, transforming them into sustainable, competitive companies with the same conditions.